Economic inequality is fueled by population scale, land-limited production, and settlement hierarchies across the archaeological record - Timothy A. Kohler; Amy Bogaard; Scott G. Ortman; Enrico R. Crema; Shadreck Chirikure; Pablo Cruz; Adam Green; Tim Kerig; Mark D. McCoy; Jessica Munson; Cameron Petrie; Amy E. Thompson; et al. (Proceedings of the National Academy of Sciences, 2025)
Defining wealth broadly to include wealth in people, relational connections, and material possessions, we examine the prehistory of wealth inequality at the level of the residential units using the consistent proxy of Gini coefficients calculated across areas of contemporaneous residential units. In a sample of >1,100 sites and > 47,000 residential units spanning >10,000 y, persistent wealth inequality typically lags the onset of plant cultivation by more than a millennium. It accompanies landscape modifications and subsistence practices in which land (rather than labor) limits production, and growth of hierarchies of settlement size. Gini coefficients are markedly higher through time in settlements at or near the top of such hierarchies; settlements not enmeshed in these systems remain relatively egalitarian even long after plant and animal domestication. We infer that some households in top-ranked settlements were able to exploit the network effects, agglomeration opportunities, and (eventually) political leverage provided by these hierarchies more effectively than others, likely boosted by efficient intergenerational transmission of material resources after increased sedentism made that more common. Since population growth is associated with increased sedentism, more land-limited production, and the appearance and growth of settlement hierarchies, it is deeply implicated in the postdomestication rise of wealth inequality. Governance practices mediate the degree of wealth inequality, as do technical innovations such as the use of animals for portage, horseback riding, and the development of iron smelting.